2019
DOI: 10.1111/wej.12507
|View full text |Cite
|
Sign up to set email alerts
|

Acetone photoactivated process: application to the degradation of refractory organic pollutants in very saline waters

Abstract: Herein, we show the first report on the degradation of hazardous organic pollutants in very saline matrice (seawater) using acetone photoactivated process at 253.7 nm. Chloral black (CB), a very persistent dye of well‐established carcinogenic and mutagenic effects, was chosen a substrate model. The photodegradation of CB was monotonically increased in the presence of acetone. About 90% of CB (25.5 µM) was removed after 30 minutes in the presence of 50 mM of acetone whereas only 30% of removal was achieved unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The quantum yield of this process is known to be high, typically in the range of 0.3-0.7 at pH values above 8 [11]. However, Bendjama et al [35] reported that the intensity of the absorbed UV254 nm light in aqueous solution increased with the increasing liquid temperature, providing evidence that chlorine photolysis (even using Suntest UV-A and B) in basic media can be increased with liquid temperature. Overall, our results show that liquid temperature plays a significant role in accelerating the degradation of RhB by combining Solar-L photolysis and chlorine in a strong basic medium.…”
Section: Process Efficiency Dependence Of Liquid Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The quantum yield of this process is known to be high, typically in the range of 0.3-0.7 at pH values above 8 [11]. However, Bendjama et al [35] reported that the intensity of the absorbed UV254 nm light in aqueous solution increased with the increasing liquid temperature, providing evidence that chlorine photolysis (even using Suntest UV-A and B) in basic media can be increased with liquid temperature. Overall, our results show that liquid temperature plays a significant role in accelerating the degradation of RhB by combining Solar-L photolysis and chlorine in a strong basic medium.…”
Section: Process Efficiency Dependence Of Liquid Temperaturementioning
confidence: 99%
“…Note that, in the above reaction scheme, Equations ( 34) and (35) were proposed as the main pathway for photogeneration of • OH radicals on the TiO 2 surface [37].…”
Section: Effect Of Tio2 Nanocatalystmentioning
confidence: 99%